DESIGN OF AN EXTENDED NONPARAMETRIC EWMA SIGN CHART - Tsai, Chen-Fang; Lu, Shin-Li; Huang, Chi-Jui (International Journal of Industrial Engineering: Theory, Applications and Practice, 2016)
<span lang="EN-US" style="font-family: "Times New Roman"; font-size: 10pt; mso-fareast-font-family: 標楷體; mso-font-kerning: 1.0pt; mso-bidi-font-weight: bold; mso-ansi-language: EN-US; mso-fareast-language: ZH-TW; mso-bidi-language: AR-SA;">Selecting the correct control chart is essential to effectively monitoring process shifts. In particularly, a nonparametric control chart is recommended over a traditional control chart when the quality characteristics of a process are unknown. In this paper, we extend the nonparametric exponentially weighted moving average (EWMA) sign chart to a double EWMA (DEWMA) sign chart <span lang="EN-US" style="font-family: "Times New Roman"; font-size: 10pt; mso-fareast-font-family: 新細明體; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-TW; mso-bidi-language: AR-SA;">to improve the detection ability in small process shifts. Simulation studies show that the nonparametric DEWMA sign chart performs better than the EWMA sign chart in detecting small process shifts, but that they perform similarly when detecting large shifts.